Geomorphological processes, forms and features in the surroundings of the Melka Kunture Palaeolithic site, Ethiopia. Issue 2 (3rd July 2019) - Maerker, Michael; Schillaci, Calogero; Melis, Rita T.; Kropáček, Jan; Bosino, Alberto; Vilímek, Vít; Hochschild, Volker; Sommer, Christian; Altamura, Flavio; Mussi, Margherita
ABSTRACT: The landscape of the surroundings of the Melka Kunture prehistoric site, Upper Awash Basin, Ethiopia, were studied intensively in the last decades. Nonetheless, the area was mainly characterized under a stratigraphic/geological and archaeological point of view. However, a detailed geomorphological map is still lacking. Hence, in this study, we identify, map and visualize geomorphological forms and processes. The morphology of the forms, as well as the related processes, were remotely sensed with available high-resolution airborne and satellite sources and calibrated and validated through extensive field work conducted in 2013 and 2014. Furthermore, we integrated multispectral satellite imagery to classify areas affected by intensive erosion processes and/or anthropic activities. The Main Map at 1:15, 000 scale reveals structural landforms as well as intensive water-related degradation processes in the Upper Awash Basin. Moreover, the map is available as an interactive WebGIS application providing further information and detail (www.roceeh.net/ethiopia_geomorphological_map/ ).